The Influence of Training and Transformational Leadership on Employee Engagement and Performance - Satria, Cecep Saptari Sonalia; Kantirahayu, Dina Subekti; Yuniawan, Ahyar (Economic and Business Horizon, 2025)
This study focuses on identifying the factors causing a decline in performance target achievement in 2022 compared to 2021 and finding solutions to improve employee performance. It aims to evaluate whether factors like motivation, target challenges, and training effectiveness contribute to the decline. By analyzing the performance appraisal system, leadership, and development programs, the study seeks to design strategies for enhancing performance at PT PLN (Persero). Additionally, the study examines the influence of training and transformational leadership on employee engagement and performance, exploring the mediating role of employee engagement in this relationship. This research uses a causal approach with purposive sampling, involving 69 employees from PT PLN's Main Distribution Unit in Central Java and DI Yogyakarta, who have been employed for at least two years. Data analysis was conducted using Structural Equation Modeling (SEM-PLS) with questionnaires as the data collection method. The results show that both training and transformational leadership positively and significantly impact employee engagement and performance. Employee engagement also significantly mediates the relationship between training and transformational leadership on performance, highlighting its critical role in enhancing overall performance.